2011
DOI: 10.1093/cid/cir065
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation Hardware-Related Infections: A Report of 12 Cases and Review of the Literature

Abstract: In this monocentric study, the median delay between deep brain stimulation implantation and infection was 28 days (range, 8-820). Infections limited to generator (n = 4) required partial hardware removal, whereas infections involving frontal or retroauricular sites (n = 7) required total removal. Surgical samples yielded Staphylococcus aureus (n = 6), Staphylococcus epidermidis (n = 2), Propionibacterium acnes, and Micrococcus species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 11 publications
1
40
0
2
Order By: Relevance
“…CSF cultures that grow Staphylococcus aureus or aerobic gram-negative bacilli are indicative of infection (strong, moderate). 29. CSF cultures that grow a fungal pathogen are indicative of infection (strong, moderate).…”
Section: Neurosurgery or Head Traumamentioning
confidence: 99%
See 2 more Smart Citations
“…CSF cultures that grow Staphylococcus aureus or aerobic gram-negative bacilli are indicative of infection (strong, moderate). 29. CSF cultures that grow a fungal pathogen are indicative of infection (strong, moderate).…”
Section: Neurosurgery or Head Traumamentioning
confidence: 99%
“…Deep brain stimulation, introduced in 1987 for the treatment of Parkinson's disease, is now being used for other conditions such as dystonia, essential tremor, and obsessive-compulsive disorder [29]. The stimulator consists of an intracranial lead, a connector, and a pulse generator that is implanted in the infraclavicular area [30].…”
Section: Deep Brain Stimulation Hardwarementioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative and late infections related to skin erosion are a major drawback in functional neurosurgery, since these almost always require hardware removal to obtain infection control [20, 24-30, 35, 36]. Consequently, interruption of the neuromodulation therapy and repeated surgical procedures imply suffering for patients and relatives.…”
Section: Discussionmentioning
confidence: 99%
“…3,9 On average, DBS hardware-related infections occur in 5% of patients and the most common site for infection, although it varies, is at the connection between the DBS leads and the extension cables or at the IPG pocket. 10 Several studies have discussed the incidence, time course, and management of DBS hardware-related skin erosion [11][12][13] and superficial and DBS hardware-related infections. 10,14 Although studies have shown the effectiveness of various prophylactic antibiotic regimens 9,15 in DBS and discussed the need for complete or partial hardware removal and attempts at hardware salvage, 3,10,[16][17][18][19][20][21][22][23][24] few have demonstrated significant salvage of DBS leads in the face of infection.…”
Section: Introductionmentioning
confidence: 99%